Causal effect of gut microbiota on juvenile idiopathic arthritis: a two-sample mendelian a randomization study - Zhang, Lian; Yang, Zhihua; Zhang, LuLu; Wei, Yanwen; Wan, Lisheng (Journal of cellular and molecular medicine, 2024)
There is increasing evidence of a significant association between the gut microbiome and juvenile idiopathic arthritis (JIA). However, whether this association is causal remains to be determined. This study was a two-sample Mendelian randomization (MR) study using publicly available genome-wide association study (GWAS) summary data to investigate the causal relationship between the gut microbiome and JIA. We used summary data on gut flora and JIA obtained from genome-wide association studies (GWAS) from MiBioGen and NHGRI-EBI, using inverse variance weighting as the main method to analyse causality in the TSMR causality analysis. To check the stability of the TSMR results, we performed several sensitivity analyses and assessed the presence of reverse causality through a reverse TSMR analysis. We calculated the degree of sample overlap where applicable. The current TSMR analyses identified four bacterial taxa associated with JIA. Specifically, two bacteria, Catenibacterium (p = 2 × 10-2) and Holdemania (p = 4 × 10-2), were negatively associated with the risk of developing JIA, suggesting a protective effect, while Olsenella (p = 1 × 10-2) and Rikenellaceae (RC9gutgroup) (p = 1 × 10-2) were positively associated with the risk of JIA, suggesting that these two bacteria may be risk factors for JIA. However, the results for Catenibacterium and Holdemania should be interpreted with caution due to instability observed in ‘leave-one-out’ sensitivity analyses. Reverse TSMR analyses found no evidence of reverse causality between JIA and gut flora. Our confirmation of a causal relationship between gut flora and JIA provides an innovative perspective for the study of JIA: targeting and modulating dysregulation of specific bacterial taxa to prevent and treat JIA.